2021
DOI: 10.3389/fimmu.2021.717483
|View full text |Cite
|
Sign up to set email alerts
|

CXCL5 Downregulation in Villous Tissue Is Correlated With Recurrent Spontaneous Abortion

Abstract: Recurrent spontaneous abortion (RSA) affects 5% of childbearing-age women worldwide. Inadequate trophoblast invasion is one of the main reasons for the development of RSA; however, the underlying molecular mechanisms for RSA have not been fully understood, and further explanation is urgently needed. C-X-C motif chemokine ligand 5 (CXCL5) is reported to contribute to the invasion of cancer cells, and its aberrant expression is associated with the cellular process of tumor pathology. Considering the high behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…A recent study indicated that CXCL1 is necessary for decidual angiogenesis during the first trimester 30 . CXCL5 was also demonstrated to promote trophoblast migration, invasion, and epithelial‐to‐mesenchymal transition through PI3K/AKT/ERK1/2 signaling pathway 31 . Similarly, CXCL8 (interleukin 8) was demonstrated to directly increase the proliferation, migration, and invasion of EVT in concomitant with promoted production of MMP2 and MMP9 32 .…”
Section: Discussionmentioning
confidence: 98%
“…A recent study indicated that CXCL1 is necessary for decidual angiogenesis during the first trimester 30 . CXCL5 was also demonstrated to promote trophoblast migration, invasion, and epithelial‐to‐mesenchymal transition through PI3K/AKT/ERK1/2 signaling pathway 31 . Similarly, CXCL8 (interleukin 8) was demonstrated to directly increase the proliferation, migration, and invasion of EVT in concomitant with promoted production of MMP2 and MMP9 32 .…”
Section: Discussionmentioning
confidence: 98%
“…A growing number of studies have shown that EMT plays an important role in embryo formation. For example, EMT has been shown to regulate embryonic stem cell differentiation, and the induction of EMT enhanced trophoblast cell invasion and migration [ 34 , 35 ]. Our results here revealed that IL-23 treatment upregulated E-cadherin expression but downregulated N-cadherin expression, implying the inhibitory effects of IL-23 treatment on EMT in trophoblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…LTA (lymphotoxin alpha) [52], CXCL5 [53], MALAT1 [54] and TMEM70 [55] have been demonstrated to function in hypertension, but these genes might be novel targets for GDM. CXCL5 has been shown to be activated abortion [56].…”
Section: Discussionmentioning
confidence: 99%